Improvement of seed shattering and dormancy in Oryza sativa L. 'Hokuriku 193' based on genetic information - Nagaoka, Ichiro (Breeding science, 2017)
In this study, we investigated the genetic basis of seed shattering and dormancy in Hokuriku 193 and bred an NIL improved these traits. Analysis of an F3 population from Hokuriku 193 × Koshihikari revealed a general correspondence between seed shattering and genotypes at the qSH1 locus, suggesting a strong influence of this locus on the seed shattering in Hokuriku 193. An F2 population from [ms-bo] Nekken 2 × Hokuriku 193 was also analyzed to identify quantitative trait loci (QTLs) for seed dormancy as measured by germination rate in the first December and March after seed harvest. The results revealed a concurrence QTLs of on chromosomes 1, 3, and 6 (qSDo1, qSDo3, qSDo6). In particular, qSDo1 and qSDo6 were considered regions worthy of active modification because they were QTL regions that promoted seed dormancy when carrying Hokuriku 193 genome regions around. SSDo_NIL, a near isogenic line (NIL) derived from Hokuriku 193 by introgressing Nekken 2 alleles only at the qSH1 locus and qSDo1, did not shatter, and its germination rate was significantly higher than that of Hokuriku 193. Yield performance was similar between SSDo_NIL and Hokuriku 193, suggesting that improvement of seed shattering and dormancy does not affect yield